The effect of single farm payments on less favoured areas agriculture in Scotland: a CGE analysis - Gelan, Ayele; Schwarz, Gerald (MTT Agrifood Research Finland, 2008)
This study quantifies impacts of common agricultural policy reform on farming in Less Favoured Areas (LFAs) in Scotland. LFAs are characterised by low agricultural productivity, because of unfavourable natural conditions, which allow only extensive farming systems such as cattle and sheep rearing. The differential impacts of the single farm payment on LFA farming is examined using a CGE modeling framework that accounts for inter-sectoral linkage effects. The simulation results indicate that the policy reform has considerably larger adverse effects on LFA farms than non-LFA farms and emphasize the need to consider spatially differential impacts in further adjustments to policy reforms taking into account local circumstances.
Keywords: Ma; Common Agricultural Policy Reform; single farm payments; decoupling; Less Favoured Areas; Scotland